Stigma shapes lesbian, gay, bisexual, transgender, and queer person's mental health and experiences with mental health services in North Macedonia. Issue 6 (3rd June 2022) - Stojanovski, Kristefer; King, Elizabeth Jane; Bondikjova, Viktorija; Mihajlov, Antonio
ABSTRACT: Purpose: There is a dearth of lesbian gay, bisexual, transgender, and queer (LGBTQ+) mental health research in Southeast Europe. Our study aimed to explore Macedonian LGBTQ+ people's mental health and their experiences with mental health services. Methods: We conducted a qualitative study with 71 LGBTQ persons in N. Macedonia in the summer of 2017. Diverse sexual orientations, gender identities, and geography were represented among participants. We used content, thematic, and narrative analyses to understand LGBTQ+ people's mental health and experiences with mental health services. Results: LGBTQ+ participants described living a 'double-life' and explained that minority stressors challenge their mental health and ability to access mental health services. Participants extensively shared unethical experiences with mental health services. Transgender participants and LGBTQ+ persons living in smaller towns described additional stigmatisation that harmed their mental health and hampered use of services. While, safe and affirming mental health services exist, they are not the norm nor readily accessible to all LGBTQ+ persons. Conclusions: Macedonian LGBTQ+ people experience mental health burdens because of societal stigmatisation. Institutional discrimination, lack of accessibility, and poor quality of services challenge LGBTQ+ people's ability to address mental health needs. Structural and community-level interventions are needed to support Macedonian LGBTQ people's mental health.